Polisemy Analysis of Song Lyric in Album ‘Position’ by Ariana Grande - Faidzun Jatur Priona; Dina Fitriana (Ruang Kata, 2026)
This study goal is to analyze the types and meanings of polysemy found in Ariana Grande’s album 'Positions'. Polysemy, as a linguistic phenomenon, refers to a single word that has multiple related meanings. The research focuses on identifying polysemous words in song lyrics and analyzing their contextual meanings based on Cruse’s theory (1986). The qualitative descriptive method was employed, and the data were collected from the official lyrics of selected songs. The findings revealed that polysemy is commonly used in Ariana Grande’s lyrics to enrich the aesthetic and emotional value of the songs. The dominant type of polysemy found was contextual polysemy, where words convey meanings dependent on the song’s narrative and tone. This study contributes to semantic analysis in linguistics and provides insights into how pop music employs polysemy to create artistic ambiguity and emotional resonance.